The implementation of fintech: Efficiency of MSMEs loans distribution and users’ financial inclusion index - Pambudianti, Feronica Fa Rozalyne; Purwanto, Budi; Maulana, Tubagus Nur Ahmad (Jurnal Keuangan dan Perbankan, 2020)
The importance of understanding the efficiency of lending MSMEs through fintechpeer-to-peer lending (P2P Lending) and increasing the financial inclusion index ofits users (for lenders in particular). We use case studies on the accelerant platformwith grounded research methodology for data collection, estimation of technicalefficiency and intermediation through Data Envelopment Analysis (DEA). Descriptiveanalysis is used to investigate the determinants that influence the financialinclusion index of acceleration users. We indicate that technical efficiency has a muchsmaller value than the efficiency of intermediation with a strategy required to improvebusiness optimization and steer clear from any conditions of constant to return.In addition, factors considered in the strategy-making are loan period whichhas a positive effect on the business efficiency and non-performing loans that are notaffected by intermediacy efficiency as well as strategies to improve the index offinancial inclusion as targeted by the Financial Services Authority through the StrategyNational Financial Inclusion. In other words, the index of financial literacy,income level, and index of fintech knowledge have a positive effect on the financialinclusion index.JEL classification: D83, G23, O33 How to Cite:Pambudianti, F. F. R., Purwanto, B., Maulana, T. N. A. (2020). The implementation of fintech: Efficiency of MSMEs loan distribution and users’ index of financial inclusion. Jurnal Keuangan dan Perbankan, 24(1), 68-82.DOI: https://doi.org/10.26905/jkdp.v24i1.3218